ANALISIS TINGKAT KUALITAS KEPUASAN ANGGOTA PADA KOPERASI PEGAWAI REPUBLIK INDONESIA UNIVERSITAS RIAU - Juli Arianti Juli Arianti; Suarman Suarman '; Hardisem Syabrus Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted to analyze the quality level of satisfaction of members on Employee Cooperative Republic of Indonesia Riau University. Population of this research are all members of the Employees Cooperative Republic of Indonesia Riau University. The sample used in this study were 94 respondents. Data analysis technique using analysis Importance Performance Analysis (IPA) and Custumer Satisfaction Index (CSI). The results showed that most members feel quite satisfied with the services provided Employees Cooperative Republic of Indonesia Riau University. Seen from the results of testing the level of member satisfaction with the method of Importance Performance Analysis (IPA) there are 5 attributes included in quadrant A (top priority), which means considered important by members but not maximized or not satisfactory. While the analysis of Customer Satisfaction Index (CSI) which is equal to 59.6%, which means quite satisfiedKey words: Member Satisfaction, Importance Performancee Analysis (IPA), Customer Satisfaction Index (CSI).